Externalization of an endogenous chicken muscle lectin with in vivo development (The Rockefeller University Press, 1981)
Chicken-lactose-lectin-I (CLL-I), an endogenous lectin that is developmentally regulated in embryonic muscle, was localized by immunohistochemical techniques in tissue samples taken at various stages of in vivo development and in primary muscle cultures. Lectin, which was diffusely distributed in myoblasts, became localized in myotubes in a distribution similar to that of the sarcoplasmic reticulum and T tubules. Later in development, lectin was predominantly extracellular. This sequence suggests that externalization may have occurred by migration in the T tubules, which are continuous with the extracellular space, although alternative explanations are possible. Only traces of lectin were found in the adult. These studies did not reveal the function of CLL-I in muscle development. However, we infer that it acts by organizing complementary glycoconjugates in the intracellular tubular network, on the muscle surface, and/or in extracellular materials.